Research on the Constructing the Holistic Thinking Mode and Teaching Effect of Pharmacology - Cheng, Lu-Feng; Kang, Jin-Sen; Xu, Qi (Indian Journal of Pharmaceutical Education and Research, 2021)
Context: As a bridge course between basic medicine and clinical medicine, pharmacology is a compulsory course for students majoring in clinical medicine. Aim: The purpose this teaching is to establish a holistic thinking mode, build student-centered curriculum system by optimizing the teaching design based on the network platform. Design: Construct receptor-based teaching mode. They are based on the network platform, helping students establishing the holistic thinking of medicine. The study included undergraduate clinical medicine class from 2017 to 2019, which was randomly divided into an experimental group with holistic thinking mode instruction and a control group with conventional instruction. The teaching effect was reflected by comparing the test scores of two groups. Methods: By using PBL, CBS or classroom discussion methods to connect all lectures with fundamental questions related to knowledge points, help student establish the logical thinking of the holistic view of “Pharmacology”. Student test scores was expressed in the form of x–±SD). One-way ANOVA was used for the comparison between the two groups and SPSS 17.0 statistical software was used for statistical analysis. Results: The results shows that the phased, mid-term and final examination of the experimental class are significantly higher than those of the controls in 2017 (P < 0.05). With the increased using holistic thinking teaching mode among students, the final examination scores have improved steadily (P < 0.05). Conclusion: The receptor-based teaching mode, which are helpful to construct the overall pharmacological thinking and improve the teaching effect.
Keywords: Pharmacology; Holistic thinking; Receptor-based; Network platform; Teaching effect